(untitled) (Research, Society and Development, 2021)
In the no-tillage system, soils generally exhibit some degree of compaction that limits agricultural production. In this scenario, the use of soil cover plants is one of the alternatives capable of improving the structural quality of the soil and increasing the productivity of crops, such as soybeans. In the context, the objective of this study was to evaluate the effect of plant cover species and management systems on the improvement of the physical characteristics of a Oxisol and its effects on the production and content of soybean oil. The treatments consisted of control, no-tillage system with gypsum, chiseling system, and 12 treatments with soil cover species composed of 6 summer species and 6 winter species, in completely randomized design. Soil samples were collected in the 0-0.1; 0.1-0.2 and 0.2-0.3 m layers for determination of bulk density (BD), total porosity (TP), microporosity, macroporosity, and saturated soil hydraulic conductivity (Ksat) in 2014, 2017, 2018. Grain yield, oil content, thousand-seed weight, mean plant height and number of plants per meter were evaluated in soybean crop. Mean treatment values were compared by Tukey’s test at 5% significance. Five months after the chiseling system, there was no influence on BD. The treatments did not present differences six months after the application of gypsum. BD, TP, micro and macroporosity and Ksat were the variables most influenced by the periods of the year in the three soil layers. Grain yield, oil content, thousand-seed weight, plant height and number of plants per meter were influenced by the seasons.